Aesthetic rehabilitation with immediate implant placement in anterior maxilla after traumatic avulsive injury. A case report - Fahad Umer; Saqib Habib (Journal of the Pakistan Medical Association, 2021)
Traumatic oral injuries present their own unique restorative challenges to the clinician due to their variable clinical presentation. In such cases, achieving optimum aesthetics and function in the maxillary aesthetic zone is challenging. This case report describes the rehabilitation of a patient with immediate implant placement after suffering trauma to the oral cavity resulting in a complete loss (avulsion) of a permanent central incisor tooth. In order to preserve the existing soft and hard tissue and to achieve predictable and aesthetically pleasing results, we decided to place an immediate implant as opposed to replantation of the avulsed tooth. Flapless implant surgery was planned and a dental implant (Bio horizons Implant Systems, Inc.) was placed following non-submerged protocol. At six month’s follow-up, the clinical and radiographic examination revealed a well osseo-integrated implant with an intact buccal cortical plate. Continuous...